Future Visions for Water and Cities : A Thought Piece (London, 2015)
This paper sets out 5 different visions for water management in future cities, and explores the research and innovation challenges to achieve them.
Keywords: Desarrollo sostenible; Prospectiva; Recursos naturales; Medio ambiente; Reino Unido